PENILAIAN KINERJA KEUANGAN PERUSAHAAN DENGAN MENGGUNAKAN METODE EVA (ECONOMIC VALUE ADDED) PADA PT. TELEKOMUNIKASI INDONESIA Tbk - Mispiyanti Mispiyanti (JIAK : Jurnal Ilmiah Akuntansi dan Keuangan, 2015)
This study aims to determine the level of EVA at PT. Telekomunikasi Indonesia Tbk in the period 2011-2013. In terms of financial statement analysis, the level of EVA (Economic Value Added) generated by PT. Telekomunikasi Indonesia Tbk experienced a ups and downs and produced a positive EVA (> 0) 386,452,233, this means that there was an additional value to the company. In 2012 EVA value increased from the previous year by 3.8% to 1,861,602,233. In 2013 EVA values decreased by 0.71% to 534,194,721